Comparison of Gut Microbial Diversity in Beijing Oil and Arbor Acres Chickens - Chen,ZM (2018)
ABSTRACT The Beijing oil (BJO) chicken is an autochthona Chinese breed which shows outstanding meat quality characteristics compared with fast-growing imported chickens such as Arbor Acres (AA) chickens. Gut microbial diversity has been shown to influence host factors such as energy and nutrient metabolism, immune response and fertility. Consequently, it is hoped that analyses into host microbial populations will ultimately help to improve the quality of associated meat products. Two distinct chicken breeds, Arbor Acres (AA) and Beijing oil (BJO), were selected to analyze the composition of the 16S rRNA gene V3-V5 hypervariable regions using high-throughput sequencing technology. Upon elucidation of gut-colonizing bacteria, the Firmicutes were observed to encompass the dominant phylum. The abundance of Firmicutes in the BJO chickens (84.9%) was lower than in the AA chickens (89.9%). Conversely, the prevalence of Proteobacteria was 4.8% in BJO chickens, with a significantly lower abundance observed in AA chickens (1.3%). In the cecum, the Firmicutes were once more the dominant phylum in BJO chickens (60.2%) and AA chickens (63.7%). The abundance of bacteroidetes was 37.7% in BJO chickens and 34.9% in AA chickens, respectively. These discoveries provide a perception into the composition of the gut microbiotain both breeds. The study also provides a foundation for future research relating to gut bacterial factors that may influence the development and progression of gastrointestinal disease in chickens and other animals.